Understanding and Predicting Social Media Use Among Community Health Center Patients: A Cross-Sectional Survey - Hanson, Carl L; West, Josh; Thackeray, Rosemary; Barnes, Michael D; Downey, Jordan (Journal of Medical Internet Research, 2014)
BackgroundThe use of social media by health care organizations is growing and provides Web-based tools to connect patients, caregivers, and providers. ObjectiveThe aim was to determine the use and factors predicting the use of social media for health care–related purposes among medically underserved primary care patients. MethodsA cross-sectional survey was administered to 444 patients of a federally qualified community health center. ResultsCommunity health center patients preferred that their providers use email, cell phones for texting, and Facebook and cell phone apps for sharing health information. Significantly more Hispanic than white patients believed their providers should use Facebook (P=.001), YouTube (P=.01), and Twitter (P=.04) for sharing health information. Use and intentions to use social media for health-related purposes were significantly higher for those patients with higher subjective norm scores. ConclusionsUnderstanding use and factors predicting use can increase adoption and utilization of social media for health care–related purposes among underserved patients in community health centers.